Bridging the knowledge disparity: Success story from a Chinese translation and co-publishing endeavor - Ramaswamy, Mohan; Schenck-Hamlin, Donna (My University, 2005)
Kansas State University Libraries’ successful experience in a translation and co-publishing project was discussed in this presentation. This summaryof the presentation describes how substantial knowledge was brought from China and shared with the western world when the information was much needed. Not only the technology and the Internet, but also the human interface i.e. subject experts, librarians and translators played a vital role in this project. Thus this paper bears relevance to globalization of information in agricultural sciences.
Summary of the paper presented at the International Association of Agriculture Information Specialists (IAALD) & United States Agricultural Information Network (USAIN) Joint Conference, May 14-19, 2005, Lexington, Kentucky.
Keywords: Translation project; Invasive pest literature; Grant funded project; Literature services